Perceptions of a Partner's Spending and Saving Behavior and Financial Satisfaction - John Grable; Michelle Kruger; Jamie Lynn Byram; Eun Jin Kwak (Journal of Financial Therapy, 2021)
The purpose of this study was multifaceted. The first purpose was to test a relatively new scale—the Spender-Saver Perception Scale (Kruger, 2019)—to determine if perceptions of one’s marriage or cohabitation partner’s spending and saving behavior can be used to describe the subjective financial satisfaction of the one making the appraisal. The second purpose was to determine in an exploratory manner whether perceptions of spending and saving differ by the gender of someone in a marital or committed cohabitating relationship. Data for the study were obtained from an online survey of 313 adults. Partner perceptions were evaluated using a scale developed by Kruger (2019), whereas financial satisfaction was measured using a 10-point subjective self-evaluation item. Respondents were categorized into one of three spender and saver groups: (1) those who perceived their partner as a spender, (2) those who perceived their partner as a saver, and (3) those who perceived their partner somewhere between a spender and saver. It was determined that perceiving one’s marital or cohabitating partner as a spender was not associated with the financial satisfaction. However, perceiving one’s partner as a saver was found to be positively associated with financial satisfaction for the person making the assessment.
Keywords: spending; saving; financial satisfaction; financial knowledge; spender-saver perception scale